Pengalihan Akad Pada Pembiayaan Multijasa Di KSPPS Marhamah Wonosobo - Apriliyani, Virastuti (Program Studi Hukum Ekonomi Syariah, 2022)
Financing in KSPPS Marhamah Wonosobo in avoiding non-performing financing carried out credit rescue through restructuring actions by transferring contracts in multi-service financing with ijarah contracts to rahn tasjily (extending the installment period according to the agreement). Therefore, how is the transfer of contracts in multi-service financing to the settlement of non-performing financing at KSPPS Marhamah Wonosobo. This type of research uses qualitative research methods and has a field research type. Based on the research conducted, KSPPS Marhamah Wonosobo in transferring contracts in multi-service financing with the aim of, firstly, to overcome non-performing financing in multi-service financing that has matured and there are still remaining principal costs by intensive billing and restructuring of financing by transferring contracts in multi-service financing with an ijarah contract, the second is based on the analysis of Islamic law, namely the DSN MUI Fatwa No.44/DSN-MUI/VIII/2004 concerning Multiservice Financing, the second is the DSN MUI Fatwa No.112/DSN-MUI/2017 concerning the Ijarah contract. Based on the rules set to minimize the risk of non-performing financing, what is done is transferred to a rahn tasjily contract based on the DSN MUI Fatwa No. 68/DSN-MUI/III/2008 concerning Rahn Tasjily.